Text Classification Using Centroid Technique (International Journal of Engineering and Computer Science, 2017)
During these days, till now there is no classifier used for classification of Punjabi documents. Here we have some Punjabi news article facts, which we have necessity to examine with the use of algorithms. Punjabi is an Indo Aryan language spoken in west Punjab (Pakistan) and East Punjab (India). So just a little work has been done in Text Classification for Punjabi language. In this work, assigns to the centroid technique for text News classification to construct structure for Punjabi Language. Huge News is accustoming for training and testing persistence of the classifiers. Language detailed pre-processing technique are beneficial for raw data to originate an identical or reduced-feature lexicon. Punjabi language is a morphological amusing language which makes those responsibilities complicated and hard to do. Statistical physical characteristics of bulk and lexicon are dignified which demonstrate satisfactory and appropriate results and consequences of text pre-processing of each distinct portion. We are residue able to get satisfactory and sufficient out comes or exertion using centroid Classifier. This research paper to reveal the centroid text News classification system to fix firmly for Punjabi Language. News quantity is accustomed for training and analysis purpose of the classifiers. Punjabi language is morphological rich language which originates those jobs and trustworthy complex. Statistical features of body and lexicon are measured which show acceptable results of text pre-processing section. We are able to get appropriate/competent out comes using centroid Classifier Algorithm